Firing costs in a New Keynesian model with endogenous separations - Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2009)
This paper introduces productivity dependent firing costs in an endogenous separation New Keynesian model. By strictly respecting the bonding critique, we show that firing costs tend to increase the performance of the model along the labor market dimension but fail along the persistence dimension. Furthermore, we show that on the one hand the model needs high - unrealistic high - values of the firing costs to generate the Beveridge curve while on the other hand we are not able to find this relation in the data.
More recent version: http://hdl.handle.net/10419/130550
Keywords: E24; E32; J64; 330; Beveridge Curve; Productivity Dependent Firing Costs; Beveridge-Kurve; Kündigung; Kosten; Produktivität; Ungleichgewichtstheorie; Theorie